THE INFLUENCE OF PROFITABILITY, LEVERAGE AND DIVIDEND POLICY ON STOCK PRICES - Anatia Agusti; Hari Sriwijayanti; Devi Edriani (JURNAL ECONOMICA : Research of Economic And Economic Education, 2025)
The aim of this research is to explore how profitability, leverage, and dividend policy influence stock prices. This study focuses on mining firms that are listed on the Indonesia Stock Exchange from 2019 to 2023. It utilizes quantitative data, specifically secondary data gathered through documentation methods. The analysis includes all 62 mining companies listed on the Indonesia Stock Exchange during the period of 20192023. From these, 16 companies were chosen using specific criteria (purposive sampling). The analytical method employed in this research is multiple linear regression, with hypothesis testing carried out using SPSS software. Findings from the ttest indicate that profitability positively and significantly impacts stock prices of mining companies listed on the Indonesia Stock Exchange during 20192023, while leverage negatively and significantly affects these stock prices. Moreover, dividend policy also positively and significantly influences stock prices in the mining sector for the same period. The overall contribution of profitability, leverage, and dividend policy to stock prices is determined to be 41. 6%. JEL Classification: G30; G32; G35; G12 Keywords: Profitability, Leverage , Dividend Policy, Stock Price